Analysis of Changes in Financial Relationships in the Management of Dau and Dak Based on Law No. 33 of 2004 concerning Financial Relations Between the Central Government and Regional Governments - Fiawati, Meri Murda (Riwayat: Educational Journal of History and Humanities, 2023)
The General Allocation Fund (DAU) and Special Allocation Fund (DAK) are the main sources of funds from the central government to finance daily operational activities contained in the APBD calculation. Regulations regarding DAK and DAU are regulated in Law No. 33 of 2004 concerning Financial Balance Between the Central Government and Regional Governments, since 2022 there has been an amendment through Law No. 1 of 2022 concerning Financial Relations Between the Central Government and Regional Governments which was passed on January 5, 2022. The amendment of this law is important to do considering that the provisions in Law 33/2004 concerning Financial Balance between the Central Government and Regional Governments have not been able to solve the problem of social inequality in the regions and the rules regarding transfers to regions of the DAU and DAK types still raise social inequality problems such as uneven public services, the inability of the bureaucracy to achieve public welfare indicators. therefore there are fundamental changes between Law No. 33 of 2004 and Law no. 1 of 2022 on transfers to DAU and DAK regions . This type of research uses a normative juridical approach by examining library materials and data, such as related laws and regulations. This study aims to determine the urgency of Law No.1 of 2022 in relation to achieving the objectives of the state and to conduct a detailed comparison of arrangements in this Law related to the purpose of DAU with the type of division based on groups of regions as well as from the population of the region and others, for DAK there are objectives that are prioritized such as accelerating regional development.